An asymmetric AC electric field of triboelectric nanogenerator for efficient water/oil emulsion separation. (December 2021) - Yang, Di; Feng, Yange; Wang, Bingqiao; Liu, Ying; Zheng, Youbin; Sun, Xiao; Peng, Jialiang; Feng, Min; Wang, Daoai
Abstract: The presence of water in lubricating oil causes the latter's failure and wastage, thus greatly accelerating the corrosion and wear of mechanical equipment. It may even cause mechanical failure, which poses a challenge in water-in-oil (W/O) emulsion separation. In this work, a nylon and polyvinylidene fluoride (PVDF) electrospun nanofiber-based triboelectric nanogenerator (TENG) with an asymmetric AC electric field is designed for efficient W/O emulsion separation. Double polyimide (PI) films are used as the transition layers for charge storage in the TENG to achieve a stable short-circuit current up to 115 μA and output voltage of 2847 V, which help to realize the dehydration and separation of lubricating oil with low energy consumption and effective energy reuse. Under an asymmetric alternating voltage output of 2500 V powered by the proposed TENG, the moisture content of the W/O emulsion can be reduced from 5 wt% to 0.15 wt%, and the W/O emulsion separation rate can reach 96.97% after 30 min. The rapid separation of large amounts of W/O emulsion driven by wind could be also achieved. The working mechanism of high W/O emulsion separation efficiency driven by the asymmetric AC electric field was attributed to the dipole coalescence, oscillation coalescence and electrophoretic coalescence. Moreover, electrical breakdown hardly occurs during the working process of the TENG, and oil-water separation driven by the TENG has the characteristics of high efficiency, low cost and safety, which has promising potential to use triboelectric nanogenerator to treat oily wastewater in the actual industry in the future. Graphical Abstract: An asymmetric AC electric field powered by an electrospun nanofiber-based TENG driven by wind in nature was used for efficient W/O emulsion separation. The working mechanism of the asymmetric AC electric field powered by TENG for W/O emulsion separation has the synergistic effect of dipole coalescence, oscillation coalescence, and electrophoretic coalescence. This research provides a new and effective oil–water separation strategy, which offers great promise in the purification and emulsion separation of industrial lubricants. ga1 Highlights: Electrospun nanofibers serve as the triboelectric layer to achieve an asymmetric AC electric field. The synergistic effect of dipole coalescence, oscillation coalescence and electrophoretic coalescence. The rapid separation of large amount of W/O emulsion driven by wind could be achieved. Oil-water separation driven by TENG has effective energy reuse, low cost and safety.